Anti-diabetic effect of red quinoa polysaccharide on type 2 diabetic mellitus mice induced by streptozotocin and high-fat diet - Zang, Yanqing; Ge, Yinchen; Cao, Yang; Tang, Huacheng (Frontiers in Microbiology, 2024)
The purpose of this study was to explore the mechanism of red quinoa polysaccharide (RQP) in alleviating type 2 diabetes (T2D) through in vivo and in vitro experiments. Results of HPLC and FITR showed that RQP was a complex polysaccharide and contained more glucose, galactose and acarbose. In vitro experiments, RQP showed strong antioxidant capacity and inhibition on α-amylase and α-glucosidase.In vivo experiments, RQP was proved to induce a significant improvement of diabetes after 4 weeks of ingestion, including the abilities of lowering blood glucose, regulating lipid metabolism, anti-oxidation and promoting secretion of SCFAs. Furthermore, 16S rRNA study demonstrated that RQP transformed the intestinal microbiota composition in diabetic mice, decreased the abundance of norank_f_Muribaculaceae and Lachnospiraceae_NK4A136_group, and increased the relative abundance of Akkermansia, unclassified_f_Lachnospiraceae, norank_f_Eubacterium_coprostanoligenes_group, unclassified_f_Atopobiaceae and norank_f_Lachnospiraceae. The biosynthetic pathways, metabolic pathways and intestinal microbiome phenotypes in mice also changed accordingly. In conclusion, this study suggests that RQP can inhibit the development of diabetes by correcting the imbalance of intestinal flora.